2010
DOI: 10.1016/j.bmcl.2009.10.020
|View full text |Cite
|
Sign up to set email alerts
|

Conformationally-restricted amino acid analogues bearing a distal sulfonic acid show selective inhibition of system over the vesicular glutamate transporter

Abstract: A panel of amino acid analogs and conformationally-restricted amino acids bearing a sulfonic acid were synthesized and tested for their ability to preferentially inhibit the obligate cysteine-glutamate transporter system xc− versus the vesicular glutamate transporter (VGLUT). Several promising candidate molecules were identified: R/S-4-[4′-carboxyphenyl]-phenylglycine, a biphenyl substituted analog of 4-carboxyphenylglycine and 2-thiopheneglycine-5-sulfonic acid both of which reduced glutamate uptake at system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
11
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…In contrast to ibotenate or QA, 4‐ S ‐CPG was essentially inactive as a S x c ‐ substrate when examined in the fluorometric exchange assay (Patel et al ., 2004). More recently, a 4‐ S ‐CPG derivative in which the distal carboxylate was replaced with a sulphonic acid (4‐ S ‐SPG) was also found to inhibit S x c ‐ (Etoga et al ., 2010). Unlike the analogous anionic substitution between l ‐Glu and l ‐homocysteate, 4‐ S ‐SPG was markedly less potent than 4‐ S ‐CPG, inhibiting uptake even less effectively than l ‐Cys 2 .…”
Section: Pharmacologymentioning
confidence: 99%
“…In contrast to ibotenate or QA, 4‐ S ‐CPG was essentially inactive as a S x c ‐ substrate when examined in the fluorometric exchange assay (Patel et al ., 2004). More recently, a 4‐ S ‐CPG derivative in which the distal carboxylate was replaced with a sulphonic acid (4‐ S ‐SPG) was also found to inhibit S x c ‐ (Etoga et al ., 2010). Unlike the analogous anionic substitution between l ‐Glu and l ‐homocysteate, 4‐ S ‐SPG was markedly less potent than 4‐ S ‐CPG, inhibiting uptake even less effectively than l ‐Cys 2 .…”
Section: Pharmacologymentioning
confidence: 99%
“…6 Recently, Tsukamoto and co-workers explored the structure–activity relationship (SAR) of sulfasalazine and susalimod (SM) 7 analogs determined that the carboxylic acid is essential and that the diazo linker can be replaced with an alkyne, but that reduction to the alkene or alkyl tether lowered or abolished activity. Studies aimed at the development of 18 F-propyl-L-glutamate as an Sx c − PET imaging agent demonstrated that the S , S -isomer had superior binding affinity to the R , S -, 8 consistent with earlier observations that the transporter exhibits stereoselectivity of action.…”
mentioning
confidence: 99%
“…Aryl- and heteroaryl sulfonic acid analogs, however, yielded only a few blockers with the desired selectivity. 16 Further examination of Sx c − specificity indicated that substituting a heterocyclic carboxylic acid isostere in place of the γ-carboxylate (ibotenate, quisqualate) yielded potent inhibitors. 17 Likewise, the inhibition of VGLUT may be accomplished with structures that incorporate a non-basic nitrogen (e.g., aniline, quinoline, etc.)…”
mentioning
confidence: 99%
“…This observation is consistent with work demonstrating that VGLUT interacts more strongly with glutamate analogs that contain non-basic amines. 16 …”
mentioning
confidence: 99%
See 1 more Smart Citation